The impact of psychiatric diagnoses on two-year outcomes in patients with ventricular assist devices. (14th October 2021) - Tolia, S; Ahmed, S; Adams, J; Morreale, C; Paliga, R; Aicher, T; Coyle, L; Narang, N; Pillarella, J; Joshi, A; Sciamanna, C; Tatooles, A; et al.
Abstract: Background: A multi-specialty approach is required during patient selection for left ventricular assist device (LVAD) implantation. In addition to a comprehensive medical evaluation, patients undergo an extensive psychiatric work up to ensure their candidacy when pursuing durable support devices. We aim to analyze the impact of psychiatric illnesses on 2-year outcomes after VAD implantation. Methods: This study was a single center, retrospective analysis of 263 patients who underwent durable LVAD implantation between 2015 and 2017. All patients were evaluated by a single specialist during their work up for LVAD implantation. Patients who had a pre-existing diagnosis defined by criteria outlined in Diagnostic and Statistical Manual of Mental Disorders (DSM-5) were assigned to the History of Psychiatric Diagnosis group. Statistical analysis was performed using Chi-Square and Student's t-tests, wherein p<0.05 was considered statistically significant. Results: Of the 263 patients, 68 patients were found to have a history of psychiatric illness compared to 195 who had no previous diagnosis. Of those with a psychiatric history, 30.8% had Depression, 1.5% had Bipolar disorder, 22.1% had Anxiety, 1.5% had PTSD, and 16.2% had more than one diagnosis. 19.5% of patients with no history went on to be transplanted compared to 22.1% of patients with a psychiatric history (p=0.65). No significant difference was found between length of stay, days to readmission, 30-day survival, and 2-year survival. Patients without a psychiatric history were found to have fewer number of readmissions over 2 years (p<0.01) (See Table). No significant difference was seen in complications including driveline infections, bacteremia, cerebrovascular accidents, pump thromboses, pump hemolysis, or major bleeding events (See Table). Conclusion: Psychosocial characteristics play a significant role in determining a patient's candidacy for LVAD implantation. Although patients with a history of psychiatric illness were found to have a greater number of readmissions, this did not correlate to poorer outcomes or increased morbidity and mortality over 2 years. This study highlights the importance of taking a multi-faceted approach when determining patient eligibility for mechanical support devices. Future studies with larger population models should be conducted. Funding Acknowledgement: Type of funding sources: None.